Performance Evaluation of Non Functional Requirements (Global Journal of Computer Science and Technology, 2013)
Requirement engineering (RE) concerns goal identification by a system, operationalization of such goals into services and constraints, and assigning responsibilities, needs to agents including humans, devices/software. RE processes include negotiation, documentation, domain analysis, specification, elicitation, assessment, and evolution. It is difficult and critical to get high quality requirements. The paper gives a synopsis of the field of requirements engineering. RE is defined, and a brief history of main concepts and techniques is presented. The result got by using the method is very promising. It was evaluated extensively on Non Functional Requirements (NFR) dataset obtained from PROMISE repository, which is publicly accessible.
Keywords: requirement engineering; functional require-ments; non function requirements; performance